Photoconversion efficiency of In2S3/ZnO core-shell heterostructures nanorod arrays deposited via controlled SILAR cycles. Issue 7 (July 2022) - Almamari, Mohammed Rashid; Ahmed, Naser M.; Holi, Araa Mebdir; Yam, F.K.; Al-Abri, Mohammed Z.; Almessiere, M.A.; El-Badry, Basma A.; Ibrahem, M.A.; Aldaghri, Osamah A.; Ibnaouf, Khalid Hassan
Abstract: This paper reports the structures, morphologies, optical properties, and photoconversion efficiency (η%) of the In2 S3 /ZnO core-shell heterostructures nanorod arrays (IZCSHNRAs) produced via the controlled successive ionic layer absorption and reaction (SILAR) cycles. As-produced samples were characterized using XRD, FESEM, TEM, UV-Vis, PL, XPS and FTIR techniques. The proposed IZCSHNRAs revealed nearly double photocurrent density and η% values compared to the pure ZnO nanorod arrays (ZNRAs). In addition, the light absorption, crystallinity and microstructures of the specimens were appreciably improved with the increase of the SILAR cycles. The deposited nanoparticles of In2 S3 (ISNPs) on the ZNRAs surface was responsible for the improvement in the heterostructures, light absorption and photogenerated electron–hole pairs separation, thus enhancing the photoconversion performance. It is established that a simple SILAR approach can be very useful to produce good quality IZCSHNRAs-based photoelectrodes required for the future development of high performance photoelectrochemical cells (PECs). Highlights: In2 S3 /ZnO Heterostructures were produced via SILAR to be employed as PEC electrodes to enhance photoconversion efficiency. The effect of the various SILAR cycles on the morphologies, optics, and photoconversion of proposed IZCSHNRAs was assessed. The Type-II band was aligned using the ZnO and In2 S3 band, enabling effective carrier separation and efficient transmission. High-quality, low-cost IZCHNRAs were performed using the SILAR with low InCl3 (cationic) and Na2 S (anionic) concentrations. Abstract : PCE, IZCSHNRAs, ZNRAs, ISNPs, SILAR cycles, Photoconversion and PECs.